POTENSI PENINGKATAN PRODUKSI PISANG DALAM MENDUKUNG KEMANDIRIAN PANGAN DI DESA GEDANG-GEDANG KECAMATAN BATUPUTIH KABUPATEN SUMENEP - Amir Hamzah; R.P. Much. Muchtar; Eko Adi Sumitro (Journal of Food Technology and Agroindustry, 2022)
This study aims to determine the potential for increasing banana production in Gedang Gedang Village, Batuputih District, Sumenep Regency based on the support of internal factors and external environmental factors in Batuputih District, Sumenep Regency. The sample in this study as research subjects were 20 people taken from a population of less than 100. The data analysis used was IFE and EFE matrix analysis and SWOT analysis. The results showed that the results of the internal factor analysis obtained the weighted value of the strength factor score was 1.837 and for the weakness factor was 0.762 with a total weighted score of 2.599. This proves that internally (strengths and weaknesses) are classified as good (strong) in improving and developing banana farming in Gedang-Gedang Village. While the results of the analysis of external factors, the opportunity factor has a weight of 1.637 and the threat factor has a weighted value of 1.402 with a total external factor of 3.039. This shows that the ability to respond to opportunities in developing banana farming and being able to face threats is good. The results of the SWOT analysis on the potential strategy for increasing banana farming in Gedang-Gedang Village, Batuputih Sub-district, it is known that the proposed strategy can be concluded that the S-O (Strength-Opportunities) Strategy is to improve the banana farming system technique through training to get higher quality results and expand the network. product marketing.